What is the role of pulmonary artery pressure (PAP) estimation by Doppler echocardiography (DE) in the diagnosis of pulmonary hypertension (PHTN)?. Issue 3 (March 2016) - Teer, Bethany; Becerril‐Clas, Claudia
Abstract : Evidence‐Based Answer : DE is accurate at the population level but lacks precision in individual patients. DE estimation of a tricuspid gradient (TG) >45 mmHg has a sensitivity of 47% and specificity of 97% for the diagnosis of PHTN (SOR: B, cross‐sectional studies). DE remains the primary noninvasive tool for detection of PHTN (SOR: C, expert consensus).